Sporopollenin, a Natural Copolymer, is Robust under High Hydrostatic Pressure. Issue 22 (22nd August 2016) - Montgomery, Wren; Potiszil, Christian; Watson, Jonathan S.; Sephton, Mark A.
Abstract : Lycopodium sporopollenin, a natural copolymer, shows exceptional stability under high hydrostatic pressures (10 GPa) as determined by in situ high pressure synchrotron source Fourier transform infrared spectroscopy. This stability is evaluated in terms of the component compounds of the sporopollenin: p ‐coumaric acid, phloretic acid, ferulic acid, and palmitic and sebacic acids, which represent the additional n ‐acid and n ‐diacid components. This high stability is attributed to interactions between these components, rather than the exceptional stability of any one molecular component. This study proposes a biomimetic solution for the creation of polymer materials that can withstand high pressures for a multitude of uses in aeronautics, vascular autografts, ballistics, and light‐weight protective materials. Abstract : Lycopodium sporopollenin, a natural copolymer, shows exceptional stability under high hydrostatic pressures (10 GPa) as determined by in situ high pressure synchrotron source Fourier transform infrared spectroscopy spectroscopy. This stability is evaluated in terms of the component compounds of the sporopollenin and attributed to interactions between these components, rather than the exceptional stability of any one molecular component.